1995
DOI: 10.1002/jctb.280630107
|View full text |Cite
|
Sign up to set email alerts
|

Color removal from dye wastewaters by adsorption using powdered activated carbon: Mass transfer studies

Abstract: Color removal from synthetic dye wastewater which typically emanates from the Taiwan textile industry has been studied using powdered activated carbon (PAC) as an adsorbent. The CIE colorimetric system has been used in the measurement of color for the treatment of disperse‐red‐60 dye wastewater. The effect of contact time, dye concentrations and PAC dosage on color and color removal has been investigated. A film‐pore double resistance diffusion model for mass transfer has also been used in this study to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…1/n (13) where qe (mg g -1 ) is the amount adsorbed at equilibrium and Ce (mg L The Redlich-Peterson isotherm model is widely used as a compromise between the Langmuir and Freundlich systems, since it combines elements from both the Langmuir and Freundlich equations, where the mechanism of adsorption is a hybrid one and does not follow ideal monolayer adsorption. The Redlich-Peterson isotherm has a linear dependence on concentration in the numerator and an exponential function in the denominator [35].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…1/n (13) where qe (mg g -1 ) is the amount adsorbed at equilibrium and Ce (mg L The Redlich-Peterson isotherm model is widely used as a compromise between the Langmuir and Freundlich systems, since it combines elements from both the Langmuir and Freundlich equations, where the mechanism of adsorption is a hybrid one and does not follow ideal monolayer adsorption. The Redlich-Peterson isotherm has a linear dependence on concentration in the numerator and an exponential function in the denominator [35].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…However, most of these techniques are expensive and incapable of the complete removal of dyes from solutions. Adsorption using activated carbon (granular or powder) has shown considerable potential for dye removal owing to its large surface area, microporous structure, high adsorption capacity, simplicity of design and ease of operation [13]. However, the higher cost of this material limits its use.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ash et al bilirubin adsorbing efficacy of powdered activated charcoal is greater than of granulated charcoal, which is further supported by work from Müller showing that increased adsorption rate of bilirubin is linked to smaller adsorption particles. Decreasing the size of adsorbent particles leads to an increased concentration gradient towards the particle core as a result of a lowered internal diffusion resistance . We also found that octanoate and N‐acetyl‐tryptophanate could be removed more effectively by powdered charcoal.…”
Section: Discussionmentioning
confidence: 69%
“…However, the most widely used and the most easily reached adsorbent for dyes is activated carbon as granule or powder [145]. However, the most widely used and the most easily reached adsorbent for dyes is activated carbon as granule or powder [145].…”
Section: Adsorptionmentioning
confidence: 99%